ECONOMICS OF ZERO TILLAGE TECHNOLOGY OF WHEAT IN RICE-WHEAT CROPPING SYSTEM OF PUNJAB- PAKISTAN - M. A. Tahir; M. S. Sardar; M. A. Quddus; M. Ashfaq (Journal of Animal and Plant Sciences, 2008)
Zero tillage technology of wheat sowing is a special technique of establishing crops without tillage and seedbed preparation. Wheat is sown through zero tillage drills in the residual moisture to avoid the late sowing and save land preparation cost in rice fields irrigated in mid October. The current study was undertaken in rice growing districts; Sheikhupura, Gujranwala, Hafizabad, Sialkot, Narowal and Lahore of Punjab (Pakistan) to analyse the impact of this technology. The sample size of 162 farmers was determined by using the statistical formula suitable for unknown population. The water saving with zero tillage was not to the extent as it is claimed. There was about 2 acre inches of water saving and water use efficiency was about 13 percent higher in zero tillage as compared to conventional method. Fertilizer use efficiency was 8 percent more in conventional method. Seed rate was more or less the same in both zero tillage and conventional methods. Production Function Analysis suggests more weeds in zero tillage fields and more weedicide cost for its effective control. It was found that conventional method of wheat sowing was better and economically viable as compared to zero tillage, showing the contribution of tillage not only positive but also significant which reflects the importance of tillage operation before sowing in enhancing the yield. The average wheat yield per acre was 6.8 percent lower and net return was 4.3 percent lower in zero tillage as compared with conventional tillage. Average farm size of the sample farmers was 33.8 acres, which indicates that zero tillage has been adopted by relatively large farmers who can afford to sacrify yield by allocating some area to zero tillage to reduce the cost of cultivation. There was no evidence of early sowing of wheat, as it is claimed, enabled by zero tillage.
Keywords: Zero tillage; Weedicide; Production Function Analysis